تقييم الزبون الجزائري لأهمية الضمان في تخفيض المخاطر المدركة المرتبطة بقرار شراء سيارة - ديلمي, فتيحة (جامعة الوادي - University of Eloued, 2024)
The aim of this study was to assess the evaluation of Algerian customers regarding warranties as one of the perceived risk reduction tools associated with the decision to purchase durable goods, specifically focusing on the case of car purchases. This was conducted using a sample of 95 individuals.After statistically processing the data using SPSS V22 software, it was found that the perception of risks associated with car purchasing decisions was relatively high. Warranties were considered a moderately effective risk reduction tool, ranking below both quality and the reputation of the country of origin. Furthermore, the assessment revealed that the importance of warranties in reducing functional, financial, health-related, and psychological risks was rated as high. However, the assessment was moderate for social and temporal risks.
The Algerian customer's evaluation of the importance of warranty in reducing perceived risks associated with the decision to purchase a car
مقال
Keywords: ضمان ; مخاطر مدركة ; قرار الشراء ; منتجات معمِّرة ; سيارة; Warranty, Perceived Risks, Purchase Decision, Durable Goods, Car